MORPHOLOGICAL CHARACTERISTICS (QUALITATIVE AND QUANTITATIVE) OF CASSAVA PLANTS IN SERDANG BEDAGAI DISTRICT, NORTH SUMATRA - Setiawan, Andi; Sebayang, Nur Ulina Warnisyah (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Serdang Bedagai Regency is the largest cassava production center in North Sumatra with a production of 545,881.3 tons of cassava, but until now there was no quantitative data on the differences in morphological characteristics in the Serdang-Bedagai district. This study aimed to determine cassava diversity based on morphological traits in the lowlands of the Serdang Bedagai district of North Sumatra. The method used in this study was a survey method, namely the identification of morphological characteristics of cassava. Morphological features observed were qualitative and quantitative features. Observations were made on cassava plants planted by farmers in the Serdan Bedagai district of North Sumatra. The cassava was old enough to be harvested, healthy, and free of pests and diseases. The lowlands of Serdang Bedagai Regency have seven species: Klanting Putih (G1), Klanting Merah (G2), Jakarta (G3), Adira (G4), Malaysia (G5), Gendruwo (G6), Gendruwo Hitam (G7), Thailand (G8), dan Kuning (G9). There are differences and similarities in morphological characteristics among the nine cassava species. A relatedness analysis based on 31 qualitative and quantitative morphological features indicated the existence of plant-related groups among cassava.